The Effectiveness of a Mnemonic-Type Startle and Surprise Management Procedure for Pilots. Issue 3 (1st October 2020) - Landman, Annemarie; van Middelaar, Sophie H.; Groen, Eric L.; van Paassen, M. M. (René); Bronkhorst, Adelbert W.; Mulder, Max
ABSTRACT: Background : Mnemonic-type startle and surprise procedures were previously proposed to help pilots cope with startle and surprise in-flight, but effects on performance after procedure execution have not yet been investigated. Objective : Thus, we tested the effectiveness a new mnemonic-type procedure in a moving-base simulator with a non-linear model of a small twin-propeller aircraft flown single-pilot. Method : An experimental group of twelve line pilots was trained to use a four-item procedure: 1. Calm down : take a deep breath, sit up straight and relax shoulders and hands. 2. Observe : call out the basic flight parameters. 3. Outline : formulate a hypothesis about the problem. 4. Lead : formulate and execute a plan of action. A control group of twelve line pilots received a control training. Next, all pilots performed four scenarios with startling and surprising events. Data were obtained on pilot performance, stress, procedure application and evaluation. Results : Application of the procedure in the test scenarios was high (90.0% full, 100.0% partly), and pilots evaluated the procedure positively (median: 4 on a 1–5 point scale). There was significantly superior decision-making in the experimental group, but immediate responses were significantly less optimal. Pilots sometimes applied the procedure at inappropriate moments. Conclusion : The results of the tested mnemonic-type procedure were promising. The procedure may benefit, however, from modifications to reduce complexity and to stimulate application at the appropriate moment.